The German Federal Constitutional Court ruling and the European Central Bank's strategy - Lars P. Feld; Volker Wieland (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2020)
The ruling of the German Federal Constitutional Court and its call for conducting and communicating proportionality assessments regarding monetary policy have been the subject of some controversy. However, it can also be understood as a way to strengthen the de-facto independence of the European Central Bank. This paper shows how a regular proportionality check could be integrated in the ECB's strategy that is currently undergoing a systematic review. In particular, it proposes to include quantitative benchmarks for policy rates and the central bank balance sheet. Deviations from such benchmarks can have benefits in terms of the intended path for inflation while involving costs in terms of risks and side effects that need to be balanced. Practical applications to the euro area are provided.
Keywords: E52; E58; K10; 330; central bank independence; monetary law; monetary institutions; monetary policy strategy; proportionality; policy rules; quantitative easing